Personality traits and personal values of servant leaders. Issue 2 (29th March 2019) - Sun, Peter; Shang, Sudong
Abstract : Purpose: Servant leaders focus on their direct reports to enable them to grow to be independent and autonomous leaders. The purpose of this paper is to understand the way personal values and personality traits collectively influence this other-centered behavior. This will go a long way to unravel this unique style of leadership. Design/methodology/approach: The study surveys managers and their direct reports. Leaders rated their personality trait and personal values, while their direct reports rated the leader's servant leadership behaviors. Age, educational level, conscientiousness, extraversion and neuroticism of leaders were used as controls. The study also checked for endogeneity threats. Findings: Using a sample of 81 leaders and 279 of their direct reports, the study finds that the personal value of benevolent dependability relates negatively to servant leadership behaviors. In addition, the personality traits of agreeableness and openness/intellect moderate the relationship between benevolent dependability and servant leadership behaviors. Research limitations/implications: The findings shed important insights into what motivates servant leaders to engage in other-directed behaviors, thereby enabling future research into individual characteristics that define servant leaders. Originality/value: Although studies have examined how values and personality traits influence leadership behaviors, no research has examined both types of individual differences in a single study. Studies examining the individual differences of servant leaders are few, and this study answers the call by Liden et al. (2014) to examine individual characteristics that are both personality based (traits) and malleable (values).